Rat Paraventricular Neurons Encode Predictive and Incentive Information of Reward Cues - Munkhzaya, Unur; Chinzorig, Choijiljav; Matsumoto, Jumpei; Nishimaru, Hiroshi; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Behavioral Neuroscience, 2020)
The paraventricular nucleus of the thalamus (PVT) has been implicated in cue-induced motivated behaviors. Although reward-associated cues (conditioned stimuli, CSs) contain different types of information including predictive information of future reward delivery and incentive (motivational) value of the reward, it remains unknown whether PVT neurons represent predictive and incentive information of CSs. It is suggested that neural activity just after the onset of CSs (early activity) and that just before reward delivery (late activity) might more strongly represent predictive and incentive information, respectively. In this study, rats were trained to lick a tube, which was protruded close to their mouth just after a CS, to obtain a reward (sucrose or water) (cue-induced licking task). Auditory and visual CSs were used: each elemental cue (CS) predicted reward or non-reward outcome, while simultaneous presentation of the two elemental cues (configural cues) predicted the opposite reward outcome. We recorded PVT neurons in the cue-induced licking task, and report that half of the CS-responsive PVT neurons responded selectively to the CSs predicting reward outcome regardless of physical property of the cues (CS+-selective). In addition, the early activity of the CS+-selective neurons discriminated reward/non-reward association (predictive information) and was less sensitive to reward value and motivation reflected by lick latency (incentive information), while the late activity of the CS+-selective neurons was correlated with reward value and motivation rather than reward/non-reward association. Early and late population activity of the CS+-selective neurons also represented predictive and incentive information of the CSs, respectively. On the other hand, activity of more than half of the PVT neurons was correlated with individual licking during licking to acquire reward. Taken together, the results suggest that the PVT neurons engage in different neural processes involved in cue-induced motivated behaviors: CS encoding to determine reward availability and form motivation for reward-seeking behavior, and hedonic mouth movements during reward consumption.